Riba Usaha Koperasi: Studi Interdisipliner terhadap Legalitas Riba dalam Ulangan 23:20 dari Perspektif Preferential Option for the Poor - Terifosa Ndruru (Gema Teologika, 2025)
Abstract For a long time, the practice of charging interest on loans has been a means for capitalists to amass wealth, often at the expense of debtors who suffer economic injustice in an interest-driven economy. This is evident in the independent cooperative initiatives by some church members in Tangerang. Consequently, it is essential to examine the issue of interest from the viewpoints of economists, sociologists, and theologians. This research demonstrates that wholesale lending practices fail to enhance the economic conditions of low-income individuals. To address this, the study employs an interdisciplinary qualitative approach to explore the phenomenon as an economic, social, and theological issue. The goal of this research is to propose a solution for enhancing economic well-being without interest, drawing on Pedro Arrupe’s theory of preferential options for the poor. This theory stresses the importance of responsibility and solidarity with the impoverished by offering loans with low interest, as guided by Deuteronomy 23:20.